Home country investor protection, ownership structure and cross-listed firms' compliance with SOX-mandated internal control deficiency disclosures - Ke, Bin (2014)
We examine whether home country investor protection and ownership structure affect cross-listed firms' compliance with SOX-mandated internal control deficiency (ICD) disclosures. We develop a proxy for the likelihood of cross-listed firms' ICD misreporting during the Section 302 reporting regime. For cross-listed firms domiciled in weak investor protection countries, we have three main findings. First, firms whose managers control their firms and have voting rights in excess of cash flow rights are more likely to misreport ICD than other firms during the Section 302 reporting regime. Second, there is a positive association between the likelihood of ICD misreporting and voluntary deregistration from the SEC prior to the Section 404 effective date. Third, for firms that chose not to deregister, there is a positive association between the likelihood of ICD misreporting and the reporting of previously undisclosed ICDs during the Section 404 reporting regime. We do not find similar evidence for cross-listed firms domiciled in strong investor protection countries. Our findings are consistent with the hypothesis that, for cross-listed firms domiciled in weak investor protection countries, managers who have the ability and incentive to expropriate outside minority shareholders are reluctant to disclose ICDs in order to protect their private control benefits. The results of our study should be of interest to regulators who wish to identify noncompliant firms for closer supervision, investors who wish to identify ex ante red flags for poor financial disclosure quality, and researchers who wish to understand the economic forces governing cross-listed firms' financial disclosure behavior.